2020
DOI: 10.1080/07391102.2020.1839560
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering underlying mechanism of Sars-CoV-2 infection in humans and revealing the therapeutic potential of bioactive constituents from Nigella sativa to combat COVID19: in-silico study

Abstract: COVID-19, emerged at the end of 2019 have dramatically threatened the health, economy, and social mobility of people around the world and till date no medication is available for its treatment. An amazing herb, Nigella sativa , having antiviral, antihypertensive, anti- diarrhoeal, analgesics, and anti-bacterial properties, needs to be explored for its efficacy against SARS-CoV-2, the causative agent of COVID-19. In-silico studies were carried out to understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The constituents of N. sativa such as, α-hederin, thymohydroquinone, and TQ have efficiently binding to ACE 2 and potential therapeutic effects of these bioactive components to combat COVID-19 in-silico study was suggested (Jakhmola Mani et al. 2020 ). The affinity of TQ on SARS–Cov-2 E protein and inhibitory effects on E protein ion channel were showed in the molecular docking study (Mohideen 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The constituents of N. sativa such as, α-hederin, thymohydroquinone, and TQ have efficiently binding to ACE 2 and potential therapeutic effects of these bioactive components to combat COVID-19 in-silico study was suggested (Jakhmola Mani et al. 2020 ). The affinity of TQ on SARS–Cov-2 E protein and inhibitory effects on E protein ion channel were showed in the molecular docking study (Mohideen 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a molecular docking study, it was revealed that dithymoquinone, an active component of Nigella Sativa, possessed strong binding potential at the SARS-CoV-2 interface [13]. In another study, Nigellidine and α-Hederin exhibited the same property by binding onto 6LU7 active site and 2GTB active site respectively [14,15]. SARS-CoV-2 integral proteins such as the spike protein, angiotensin-converting enzyme 2, 3C-like cysteine protease, and papain-like protease are revealed to be good targets for drug developments [16] as α-Hederin, Thymohydroquinone, and Thymoquinone were observed to efficiently bind to ACE2 [15].…”
Section: Combatting Covid-19mentioning
confidence: 99%
“…Several in silico studies have reported pharmacological potentials of black cumin and its various compounds against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causal pathogen of recently emerged coronavirus diseases 19 (COVID-19) pandemic [ 271 , 272 , 273 ]. A line of recent reviews also revisited pharmacological potentials of black cumin in the prevention of COVID-19 and the associated complications [ 274 , 275 , 276 , 277 ].…”
Section: Benefits Of Black Cumin On Human Health and Disease Conditionsmentioning
confidence: 99%